PENGARUH INTELLECTUAL CAPITAL TERHADAP KINERA KEUANGAN MELALUI INNOVATIF CAPABILITY PADA HOTEL DAN RESTORAN DI SURABAYA - Astriana Ivony Sunur (Business Accounting Review, 2016)
This study used a quantitative approach, and the data were obtained through distributing questionnaires to hotel and restaurant in Surabaya and processed by using smartPLS software. This study showed that there was a positive and significant relationship of intellectual capital to innovative capability; innovative capability to financial performance; and intellectual captal to financial performance in hotel and restaurant in Surabaya. Innovative capability was adequate to be an intervening variable between intellectual capital and financial performance because the indirect relationship between intellectual capital and financial performance through innovative capability gave greater effect than if it was not through innovative capability.